MIGRANTS' REMITTANCES: ECONOMIC LIFELINE BUT FRAGILE SUPPORT FOR DEVELOPING COUNTRIES. THE CASE OF BELARUS, MOLDOVA AND UKRAINE (A MACROECONOMIC PERSPECTIVE) - S. Burnete (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Today's economic development on a global scale is highly dependent on the free movement of factors of production across national borders in search of highest return in case of capital, highest compensation in case of technological and managerial capabilities, biggest pay envelope, in case of physical labor and so on. Although the latter has long been hampered from moving owing, on the one hand, to deterrence policies pursued by home countries' governments, and on the other hand, to barriers erected against immigration by host countries, legions of workers of various skills and abilities managed to shift to developed countries in order to find better-paid jobs. People heading for the West generally succeeded in saving significant shares of their earnings, which they would send to their families at home. The paper contains a comparative analysis aimed at ascertaining the effects of remittances on the economies of three ex-Soviet countries: Belarus, Moldova and Ukraine.